2015
DOI: 10.5935/1678-9741.20150021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass: development of John Gibbon's heart-lung machine

Abstract: ObjectiveTo provide a brief review of the development of cardiopulmonary bypass.MethodsA review of the literature on the development of extracorporeal circulation techniques, their essential role in cardiovascular surgery, and the complications associated with their use, including hemolysis and inflammation.ResultsThe advancement of extracorporeal circulation techniques has played an essential role in minimizing the complications of cardiopulmonary bypass, which can range from various degrees of tissue injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 35 publications
1
41
0
2
Order By: Relevance
“…Previous studies also found the same results (21)(22)(23)(24). Some researchers also reported increased sodium levels after liver transplant is associated with postoperative complications (13)(14)(15)(16)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies also found the same results (21)(22)(23)(24). Some researchers also reported increased sodium levels after liver transplant is associated with postoperative complications (13)(14)(15)(16)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 72%
“…Despite several effective approaches including prone positioning and low tidal volume ventilation, acute respiratory distress syndrome [17] still has a mortality of more than 40% and affects about 10% of ICU patients. Extracorporeal lung support was introduced more than 80 years ago with Gibbon's heart-lung machine [18]. The first case reports on the clinical use of ECMO in ARDS and preterm infants were published in the 1970s.…”
Section: Extracorporeal Lung Support: Oxygenationmentioning
confidence: 99%
“…The development of the heart-lung machine in the 1930's was an important landmark for cardiac surgery as it enabled tissue perfusion while the heart was stopped and provided a bloodless field for surgery. 19 The basic cardiopulmonary bypass (CPB) circuit consists of venous cannula, tubing, reservoir, pump, heat exchanger, oxygenator, tubing, arterial cannula, and cardioplegia cannula. The system allows venous blood to be drained from the heart, oxygenated, and returned to circulation, thereby taking over the natural functions of the heart and lungs.…”
Section: Cardiopulmonary Bypassmentioning
confidence: 99%
“…The system allows venous blood to be drained from the heart, oxygenated, and returned to circulation, thereby taking over the natural functions of the heart and lungs. 19 However, there are complications associated with CPB which can be broadly divided into mechanical and systemic types.…”
Section: Cardiopulmonary Bypassmentioning
confidence: 99%